THE CATEGORY OF IRONY IN RUSSIAN LITERATURE AND CRITICISM - Kadirova N.A (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article examines the history of the study of irony in Russian literature, provides a historical digression necessary to understand the existing definitions covering the manifestations of irony in literary and artistic discourse. Irony as an aesthetic category was understood differently in different epochs, having undergone significant and significant changes.